PENDIDIKAN KESEHATAN GOOD FOOD, GOOD SLEEP, GOOD MOOD RAHASIA KOMBO HIDUP SEHAT - Bachtiar Safrudin; Kartika Setia Purdani; Cahya Indah Fitriani; Wanda Amelia N.; Cindy Maharani Dewi; Diah Maulia; Diandra Dita Raudina; Fachmi Alamsyah; Indah Prayudita; Naelan Najah; Nur Abida; Putri Sintya Wati; Rifky Rama Nur H.; Tsamarah Hanin Rana; Winna Noor Cholifah (CV. KAMPUS AKADEMIK PUBLISING, 2026)
Health significantly influences the learning quality of vocational high school students. However, many of them still have poor dietary habits, insufficient sleep, and difficulty managing their mood. The concept of